Identifying Factors Influencing Urban Bus Drivers’ Distraction: A Qualitative Study in Tehran, Iran - Fatemeh Sadat Mirnajafi Zadeh; Mojtaba Khosravi Danesh; Ali Nahvi; Abbas Rahimi Foroushani; Mohammad Javad SheikhMozafari; Adel Mazloumi (بهداشت و ایمنی کار)
Introduction: Despite advancements in road safety and vehicle design, road accidents remain prevalent, a quarter of which are caused by driver distraction. This issue is particularly critical in the public transport sector, especially among urban bus drivers, as distraction can lead to serious injuries and fatalities. Accordingly, this study explored the factors influencing distraction among urban bus drivers through a qualitative approach and a macroergonomics perspective. Material and Methods: In this study conducted in 2024 in Tehran, 18 urban bus drivers were selected through cluster sampling. The participants included 10 drivers from bus rapid transit (BRT) system and 8 drivers from non-BRT services. Data were collected through semi-structured interviews with the drivers as well as on-site observations. Subsequently, a directed qualitative content analysis approach, based on the balance theory model, was used to analyze the collected data. Results: The findings revealed that the primary sources of distraction belonged to six levels of the work system, the most cited of which were environment, tasks, and organization. Specifically, inappropriate behavior of other street users as an environmental factor and the driver’s interactions with passengers as task-related factors were identified as key sources. Additionally, organizational factors such as interactions with supervisors and colleagues, as well as salary issues, were significantly important. The participants very limitedly expressed using mobile phone while driving as a main distractor to their driving. Conclusion: The current study identified various influential factors, spanning different levels of the work system, affecting bus drivers’ distraction, including generic factors that impact all urban drivers and specific factors that uniquely affect bus drivers. Addressing these factors through providing appropriate education for both passengers and street users along with implementing management strategies in the organization to enhance intra-organizational relationships and organizational support can lead to the safety of the bus drivers.